2014
DOI: 10.5114/aoms.2014.40738
|View full text |Cite
|
Sign up to set email alerts
|

Association of dental and periodontal status with bisphosphonate-related osteonecrosis of the jaws. A retrospective case controlled study

Abstract: IntroductionTo assess the association of oral hygiene, dental caries, and periodontal status with bisphosphonate-related osteonecrosis of the jaws.Material and methodsA retrospective case-control study on 81 patients treated for neoplasms with bone metastases. Twenty-nine patients with bone necrosis and 52 controls treated with bisphosphonates were compared using the Oral Hygiene Index, Decay, Missing, Filled Teeth, Community Periodontal Index of Treatment Needs, and Residual Periodontal Bone. The null hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 42 publications
3
41
1
2
Order By: Relevance
“…A retrospective case control study by Kos showed that the percentage of patients with deep teeth pockets was significantly higher among BRONJ cases (14). …”
Section: Discussionmentioning
confidence: 99%
“…A retrospective case control study by Kos showed that the percentage of patients with deep teeth pockets was significantly higher among BRONJ cases (14). …”
Section: Discussionmentioning
confidence: 99%
“…All of the studies had been published since 2008. Six of the studies were based in Europe (two in the Germany, three in Italy, one in Greece and one in Spain), two in United States of America, one in Brazil, one in Japan and one in Australia …”
Section: Resultsmentioning
confidence: 99%
“…When BRONJ progressed into the basal bone, pathologic fracture, pus discharge and cutaneous fistula could be formed. The incidence of the BRONJ has been reported as between 0 to 28% (13)(14)(15)(16)(17). The incidence of the BRONJ in oral bisphosphonates were reported as a minimal risk.…”
Section: Discussionmentioning
confidence: 99%